1988
DOI: 10.1128/aac.32.11.1693
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial action of 2-bromo-2-nitropropane-1,3-diol (bronopol)

Abstract: Patterns of growth inhibition of Escherichia coli in the presence of 2-bromo-2-nitropropane-1,3-diol (bronopol) indicate a period of biocide-induced bacteriostasis followed by growth at an inhibited rate. The length of the bacteriostatic period, but not the subsequent growth inhibition, was reduced by the addition of excess cysteine. Patterns of growth inhibition were unaffected by catalase or superoxide dismutase. The bactericidal concentrations (100 to 500 ,ug/ml) were considerably in excess of the MIC (13 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 15 publications
(13 reference statements)
0
41
0
Order By: Relevance
“…The antibacterial mechanism of bronopol has been attributed to its interaction with essential thiols within the cell [32,33]. Shepherd et al [36] have also reported that bronopol catalyses the oxidation of thiol groups to disulfides with the consumption of oxygen. Such catalytic reaction also results in the generation of free radicals which subsequently inhibits the growth of the bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibacterial mechanism of bronopol has been attributed to its interaction with essential thiols within the cell [32,33]. Shepherd et al [36] have also reported that bronopol catalyses the oxidation of thiol groups to disulfides with the consumption of oxygen. Such catalytic reaction also results in the generation of free radicals which subsequently inhibits the growth of the bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrite, a specific metabolic inhibitor of corrosive bacteria, especially sulphate reducing bacteria [32,33], is also relatively nontoxic and inexpensive and has been successfully used to inhibit corrosive bacteria [34]. 2-Bromo-2-nitropropane-1,3-diol (bronopol) has a broad spectrum of antibacterial activity and is widely used as a preservative in pharmaceutical and cosmetic products and many industrial environments such as paper mills, oil exploration, and production facilities, as well as a disinfectant in cooling water [35,36]. The present investigation describes 16S rRNA gene sequencing and the identification of bacterial communities (at the species level) present in water from a cooling tower.…”
Section: Introductionmentioning
confidence: 99%
“…These preservatives are widely used in cosmetic preparations due to their neutral, non-irritating, non-toxic and safe to use. [24][25][26] The organoleptic study showed that there were no change in the shape, odor, and color of all formulations during storage at room temperature for 56 days. These result suggest that the essential oils were stable on corn starch-based thixogel, probably due to steady emulsion system in the corn starch-based thixogel.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, BNPD has a broad spectrum of antibacterial activity which is a non-oxidizing compound, stable under varying conditions of temperature, relative humidity and exposure to natural light, slightly toxic to avian species, freshwater fish and invertebrates [10]. The antibacterial activity of BNPD relates to its interaction with essential thiols within the cell for the growth inhibition and generation of free radicals causing cell death [11][12][13].…”
Section: Introductionmentioning
confidence: 99%